A study on the prevalence of scrub typhus among pediatric population in a rural tertiary care hospital in West Bengal - Anirban Bhaduri; Sayani Bose; Atindra Kumar (Asian Journal of Medical Sciences, 2024)
Background: Scrub typhus is a common rickettsial infection endemic in India and is an important cause of acute febrile illness among children. Clinical manifestations vary from mild-to-severe affecting almost all organ systems with a high fatality rate. To reduce morbidity and mortality, a high index of suspicion, timely diagnosis, and treatment are crucial. However, due to lack of awareness, low index of suspicion among clinicians, and non-specific clinical presentation which overlaps with other tropical endemic infections of India such as dengue, chikungunya, malaria, and leptospirosis, scrub typhus is often underdiagnosed in our country. Aims and Objectives: (1) To find the prevalence of scrub typhus among children presenting with fever for the last 5 days, (2) To study their clinico-demographic profiles. Materials and Methods: Blood collected from children aged 1 month to 12 years of age presenting with fever for the last 5 days were tested for scrub typhus immunoglobulin M enzyme-linked immunosorbent assay. Clinical characteristics and laboratory parameters of the patients were collected. The results obtained were analyzed and interpreted. Results: Out of 865 pediatric patients presenting with fever, only 227 (26.24%) were positive for scrub typhus. Maximum cases (45.37%) were found in the age group >5–12 years. Fever was the presenting feature in all the cases. Other common presentations were hepatosplenomegaly, lymphadenopathy, pain abdomen, rash, and eschar. Conclusion: Although scrub typhus is an easily treatable disease, timely diagnosis and treatment are needed to avoid complications which require a high degree of suspicion among clinicians along with a robust laboratory setup with adequate diagnostic facilities.